Genetics of preeclampsia - Quiroga de Michelena, María Isabel (2015)
Preeclampsia is a multifactorial and complex condition whose etiology continues in study.Identification of genes involved in preeclampsia may lead to markers that may predict and/ordetect preeclampsia, and the discovery of specific and personalized treatments.Keywords: Preeclampsia, genetics.